(untitled) (Academicia Globe: Inderscience Research, 2023)
Acute rheumatic fever (ARF) is a systemic inflammatory lesion of the connective tissue with a predominant localization of the process in the cardiovascular system and the musculoskeletal system. With rheumatism, any organs and systems can be affected: the brain, kidneys, liver. ARF occurs predominantly in childhood (7-15 years) and young age, and also occupies an important place in the overall structure of the incidence of cardiovascular diseases and mortality from them.